Drivers of innovation value: simulation for new drug pricing evaluation based on system dynamics modelling - Xing, Qian; Cheng, Wendi; Wang, Wei; Jin, Chunlin; Wang, Haiyin (Frontiers in Pharmacology, 2025)
ObjectivesPaying for the innovative value of drugs is an important means of mitigating healthcare system duplication and enhancing patient health. Assessing and exploiting the factors influencing innovation premium to forecast trends and shortcomings within the pharmaceutical innovation ecosystem.MethodsUtilizing system dynamics, this research constructs a decision evaluation system for new drug pricing in Japan. It integrates various decision-making factors across dimensions such as value premium, marketability premium, pediatric premium, and SAKIGAKE premium, employing Vensim PLE software for simulation purposes.ResultsUnder the current policy framework, pharmaceutical innovation is on the rise, with significant policy effects observable after 5 years. The most substantial growth in value occurs in medications for rare diseases and niche markets, with effects varying in the short to medium term and stabilizing over the long term. Sensitivity analysis highlights that factors like combination therapies, faster mechanisms of action, and novel therapeutic parts notably influence the value dimension. Other significant factors include obtaining national certifications, addressing indications lacking standard treatments, and demonstrating superior efficacy. The study also identifies underexploited opportunities related to the use of evidence in pricing decisions.ConclusionClinical outcomes are pivotal in shaping drug pricing, influencing both patient and healthcare provider preferences, and thereby affecting market uptake and competitive dynamics. Regulatory frameworks that prioritize unmet medical needs or superior drug efficacy are essential. Future enhancements to the model should incorporate more real-world evidence and expand regulatory considerations to better reflect the dynamic nature of the healthcare sector and support equitable, outcome-based drug pricing.